XUV Sources Based on Intra-Oscillator High Harmonic Generation with Thin-Disk Lasers: Current Status and Prospects - Labaye, François; Gaponenko, Maxim; Modsching, Norbert; Brochard, Pierre; Paradis, Clément; Schilt, Stephane; Wittwer, Valentin Johannes; Südmeyer, Thomas (My University, 2019)
Ultrafast thin-disk laser (TDL) oscillators provide higher intracavity pulse energy, average power, and peak power levels than any other femtosecond laser oscillator technology. They are suitable for driving extreme nonlinear interactions directly inside the laser oscillator. High harmonic generation (HHG) driven inside ultrafast TDL oscillators is a very recent approach for the generation of coherent extreme ultraviolet (XUV) light at multi-megahertz repetition rates. In this paper, we review the current state of the development, discuss the technological potential, and give an outlook toward the future developments. We compare the current performance to established technologies and evalu-ate possible limitations. We discuss future improvements, such as reduction of the driving pulse duration and increase of the intracavity peak power, efﬁcient extraction of the XUV light from the cavity, and carrier-envelope offset frequency stabilization of the generated XUV light. Due to the power scalability of the TDL concept and the possibility to operate in a spectrally broadened regime with pulse durations below the gain bandwidth limitation, intra-oscillator HHG with TDLs has a high potential for powerful table-top multi-megahertz coherent XUV light sources for science and applications.
Keywords: Mode-locked lasers; high-power lasers; nonlinear optics; XUV sources